2021
DOI: 10.1016/j.bbrc.2021.02.016
|View full text |Cite
|
Sign up to set email alerts
|

EGCG, a green tea polyphenol, inhibits human coronavirus replication in vitro

Abstract: COVID-19 pandemic results in record high deaths in many countries. Although a vaccine for SARS-CoV-2 is now available, effective antiviral drugs to treat coronavirus diseases are not available yet. Recently, EGCG, a green tea polyphenol, was reported to inhibit SARS-CoV-2 3CL-protease, however the effect of EGCG on coronavirus replication is unknown. In this report, human coronavirus HCoV-OC43 (beta coronavirus) and HCoV-229E (alpha coronavirus) were used to examine the effect of EGCG on coronavirus. EGCG trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 16 publications
7
76
0
Order By: Relevance
“…In addition, among the catechins, EGCG was the strongest inhibitor of live human coronavirus (HCoV OC43) infection (Fig. 4 d, e), which agrees with a recent report that EGCG treatment decreased the levels of HCoV OC43 viral RNA and protein in infected cell media through inhibition of 3CL-protease activity of the virus [ 45 ]. These data provide the direct evidence to support the assumption that high green tea consumption was associated with low morbidity and mortality of COVID-19 at the level of individual countries [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, among the catechins, EGCG was the strongest inhibitor of live human coronavirus (HCoV OC43) infection (Fig. 4 d, e), which agrees with a recent report that EGCG treatment decreased the levels of HCoV OC43 viral RNA and protein in infected cell media through inhibition of 3CL-protease activity of the virus [ 45 ]. These data provide the direct evidence to support the assumption that high green tea consumption was associated with low morbidity and mortality of COVID-19 at the level of individual countries [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…Following PL pro -UbV complex formation, PL pro deubiquitylation, deISGylation and protease activities were significantly hindered and viral progeny were much less infectious [98]. Smallmolecule inhibitor screens have subsequently identified the substrate-binding pocket and the ISG15 binding site of PL pro as important determinants of viral fitness and could serve as attractive targets for antiviral drug development [136][137][138][139][140][141][142]. For example, the small molecule GRL0617 is one of the most promising SARS-CoV-2 inhibitors currently being studied that sterically blocks the binding of ISG15 and ubiquitin to PL pro [137,142].…”
Section: Viral Antagonism Of Herc5 and Isgylationmentioning
confidence: 99%
“…Additionally, in our experiments, EGCG was preincubated with SARS-CoV-2 before infection of cells, ruling out its effects on non-structural proteins. EGCG was recently demonstrated to inhibit SARS-CoV-2 3CL-protease and coronavirus replication by inhibition of 3CL protease [35] , suggesting the all-round inhibitory potency of EGCG on SARS-CoV-2. Notably, we also observed that EGCG could inhibit the infection of 4 kinds of mutant S-pseudotyped lentivirus in human ACE2 overexpressing cells, indicating that ECGC has a good prevention prospect for the mutated SARS-COV-2.…”
Section: Discussionmentioning
confidence: 99%